Haematopoietic stem cell transplantation for vasculitis including Behçet's disease and polychondritis: a retrospective analysis of patients recorded in the European Bone Marrow Transplantation and European League Against Rheumatism databases and a review of the literature. Issue 2 (1st September 2006) - Daikeler, Thomas; Kötter, Ina; Bocelli Tyndall, Chiara; Apperley, Jane; Attarbaschi, Andishe; Guardiola, Philippe; Gratwohl, Alois; Jantunen, Esa; Marmont, Alberto; Porretto, Ferdinando; Musso, Maurizio; Maurer, Britta; et al.
Abstract : Objective: To evaluate the feasibility of haematopoietic stem cell transplantation (HSCT) in vasculitis. Methods: This is a retrospective analysis of patients who had received HSCT for vasculitic diseases and have been reported to the European League Against Rheumatism autoimmune disease or European Bone Marrow Transplantation ProMISe databases. Information about the disease and outcome was obtained by a questionnaire sent to the referring centres. Response of the disease to HSCT was defined as partial or complete responses according to the ability to reduce immunosuppression after HSCT. In addition, the Medline database was searched for reports on HSCT in patients with vasculitis. Results: Detailed information was obtained for 15 patients, whose median age at HSCT was 37 years. The diagnoses were cryoglobulinaemia in four patients, Behçet's disease in three patients, Wegener's granulomatosis in three patients, and undifferentiated vasculitis, Churg–Strauss angiitis, polychondritis, Takayasu arteritis and polyarteritis nodosa in one patient each. 14 patients received autologous HSCT and 1 an allogeneic HSCT as the first transplant. In three patients, further transplantation was given because of relapse. The overall response, including all consecutive transplantations (HSCT/patient, n = 1–3, median 1.3) to HSCT, was 93%, with 46% complete responses and 46% partial responses; median (range) duration of response at the time of reporting was 45 (16–84) months. Three patients died, one from advanced disease, one from cancer and one from graft-versus-host disease. The Medline search showed five other patients who were effectively treated with HSCT for vasculitic diseases. Conclusion: This retrospective study suggests that autologous HSCT is feasible for vasculitis. Its value remains to be tested in prospective controlled studies.